Characterization of Seminiferous Epithelium Stages in the Wild Javan Muntjac (Muntiacus muntjak muntjak) Using the Tubular Morphology Method - Sri Wahyuni; Gholib Gholib; I Ketut Mudite Adnyane; Muhammad Agil; Hamny Hamny; Srihadi Agungpriyono; Tuty Laswardi Yusuf (Veterinary Medicine International)
Stages of the seminiferous epithelium of the testis of the wild Javan muntjac (Muntiacus muntjak muntjak) in hard antler period were characterized based on the tubular morphology method. The number and the relative frequencies of seminiferous epithelium stages and the morphometry of germinal cell nuclei were identified microscopically. We identified eight stages of seminiferous epithelium in testicular tissue of the Javan muntjac and found that the relative frequencies of stages I to VIII were 14.87, 15.12, 17.75, 6.87, 7.37, 12.37, 13, and 12.62%, respectively. The diameter of the nuclei of germinal cells varied in each stage of seminiferous epithelium. Diplotene-stage primary spermatocytes had prominent and large nuclei ~8.97 ± 1.0 μm in stages III and IV. Pachytene primary spermatocytes appeared in most stages, except stage IV, whereas leptotene- and diplotene-stage primary spermatocytes were found in stages I and II, and III and IV, respectively. Round spermatids were observed in stages IV to VIII and in stage I but were absent in stages II and III, while elongated spermatids were observed in all stages except stage I. Our findings show that the stages of seminiferous epithelium in the Javan muntjac are similar to those found in neotropical cervids, small ruminants, and other domestic animals.